Гордость и предубеждение: роман (Джейн Остен ; перевод с английского И. С. Маршака) - Остин Джейн (2020)
Экземпляры: БС (20210112) / Инвентарный номер: РТШ54990 / Цена: / Сис.шифр: 84(4Вел) / Авт.знак: О-76 / ГРНТИ: 17.82.31 / ББК: 84(4Вел)-4